Airborne fungal spores in a sawmill environment in Palakkad District, Kerala, India - Padmanabhan S. Jothish & Themath Soman Nayar (Aerobiologia 20: 75-81, 2004., 2004)
Concentration of airborne fungal spores in indoor and outdoor environments of a sawmill in Palakkad district of Kerala, India was studied with Burkard Personal Slide Sampler from January to December 1997. Total spore concentration in the indoor and outdoor showed a 3:2 ratio. Higher spore count was observed in indoor in January and in outdoor in October. Thirty three fungal spore types were identified from the indoor and twenty six from the outdoor. Aspergillus/Penicillium, Cladosporium, Nigrospora, Ganoderma, `other basidiospores' and ascospores were the dominant components of the airspora. Aspergillus/Penicillium, the most dominant spore type in the indoor contributed 51.19 per cent and Cladosporium, the most dominant spore type in the outdoor contributed 44.75 per cent of the total spores. The study revealed high prevalence of predominantly allergenic fungal spores in the sawmill environment.